Bionika Dornaha - Druzhinina, Inna (project baikal, 2004)
Wood, this building material, was firstly used as sculptural plastic. The author decided to use it, on the one hand, because of the difficulties in fixing the round surfaces of outside walls, and on the other hand, it was a real «handwork», which turned the building into the exclusive object. Obviously, the simple decor of the first floor and the great decor of the second floor have a philosophical basis and give a unique silhouette to the building.While A.Gaudi used in his creations the touch of romanticism and modern to design a «living» house, R. Schteiner realized moral, aesthetic and spiritual basis of the human's attitude in the organic architectural form and turned to I.W. Goethe's spiritual, natural and scientific ideas.Goethe's discoveries had a great influence on the forming of the idea of organic architecture. Later L.Salliven, F.L.Right, Le Corbusier referred to his works.